2023
DOI: 10.3389/fpsyt.2023.1075250
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation in cocaine use disorder–An epigenome-wide approach in the human prefrontal cortex

Abstract: BackgroundCocaine use disorder (CUD) is characterized by a loss of control over cocaine intake and is associated with structural, functional, and molecular alterations in the human brain. At the molecular level, epigenetic alterations are hypothesized to contribute to the higher-level functional and structural brain changes observed in CUD. Most evidence of cocaine-associated epigenetic changes comes from animal studies while only a few studies have been performed using human tissue.MethodsWe investigated epig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…c Integrated visualization of functional genomic datasets for ZBTB4 and INPP5E gene loci. CUD-associated genomic variants (SNPs p<0.05 from 30 ), CUD-associated CpG sites (p<0.05 from 22 ), RNA-seq data and intron clusters (q<0.05) from the present study were visualized together with ENCODE ChIP-seq data for different chromatin marks in human dorsolateral prefrontal cortex.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…c Integrated visualization of functional genomic datasets for ZBTB4 and INPP5E gene loci. CUD-associated genomic variants (SNPs p<0.05 from 30 ), CUD-associated CpG sites (p<0.05 from 22 ), RNA-seq data and intron clusters (q<0.05) from the present study were visualized together with ENCODE ChIP-seq data for different chromatin marks in human dorsolateral prefrontal cortex.…”
Section: Resultsmentioning
confidence: 99%
“…Convergence of CUD association signals at the pathway level was evaluated by pathway enrichment analysis for GO terms using the enrichGO function on the GO "BP" ontology in the compareCluster functionality of clusterProfiler. A total of 10 gene lists were included in the input dataset: 1) CUDassociated CpG sites (N=394, p>0.001) from the EWAS of CUD 22 , genes in the CUD-associated WGCNA methylation modules 2) blue (N=9,201), 3) steelblue (N=390), 4) brown (N=5,268), 5) brown4 (N=205), 6) nominally significant DEGs (N=1,057,p<0.05), 7) genes in the CUD-associated WGCNA expression module yellow (N=2,517), 8) AS genes (N=98, q<0.05), 9) MOFA methylation weights factor…”
Section: Go Enrichment Analysis Of Cud-associated Gene Setsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, just as this study aimed to expand upon and explore the current understanding of the genetic underpinnings of SUD by utilizing transcriptomics, epigenomics offers a way to examine factors influencing alterations in the transcriptome. Research has begun to examine candidate genes of SUD that have been identified in GWAS for potential post-translational modifications [59, 60, 61, 62]. By investigating epigenetic mechanisms, such as methylation, acetylation, histone modifications, and chromosome remodeling, to name a few, we may be able to identify molecular mechanisms that drive changes in gene transcription and lead to aberrant neuroadaptations and circuitry seen in SUD.…”
Section: Discussionmentioning
confidence: 99%